MODEL OF IT ADOPTION FOR INCREASING THE MSME’S COMPETITIVE ADVANTAGE - Nurhadi Nurhadi (Journal of Economics, Business, and Accountancy Ventura, 2013)
In the emerging global market context, the adoption and use of information technology (IT) iswidely seen as critical for the competitiveness of Micro, Small and Medium Enterprises(MSMEs). This study aims to describe: the degree of IT adoption; the reasons to use IT; theinhibiting factor of IT adoption; and the pattern of IT adoption for MSMEs. This study is adescriptive research. The population is MSMEs registered in the Bag and Suitcases IndustryCooperative (INTAKO) Sidoarjo. Sampling method was a purposive sampling. Data was collectedusing interview technique and questionnaire, than analyzed by the descriptive statisticaltechniques. The results show that the adoption of IT for MSMEs is relatively low. Themain reasons for MSMEs to adopt the IT are the benefits of IT to increase company competitivenessand performance and the encouragement of external factors. The inhibiting factorsfor MSMEs to adopt IT are cost and human resources constraints, and the complexity of IT.Four factors determining the IT adoption for MSMEs are individual characteristics, characteristicsof technology, corporate context and environmental context. Furthermore, the lowdegree of IT adoption of MSMEs lead the IT adoption can not provide a significant improvementof the enterprise competitiveness.